2014
DOI: 10.1186/s13059-014-0526-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined image and genomic analysis of high-grade serous ovarian cancer reveals PTEN loss as a common driver event and prognostic classifier

Abstract: BackgroundTP53 and BRCA1/2 mutations are the main drivers in high-grade serous ovarian carcinoma (HGSOC). We hypothesise that combining tissue phenotypes from image analysis of tumour sections with genomic profiles could reveal other significant driver events.ResultsAutomatic estimates of stromal content combined with genomic analysis of TCGA HGSOC tumours show that stroma strongly biases estimates of PTEN expression. Tumour-specific PTEN expression was tested in two independent cohorts using tissue microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 42 publications
4
89
0
1
Order By: Relevance
“…4A). Because the IHC analysis does not take into account the confounding factor of PTEN expression in the tumor stroma, 18 we also evaluated the association of PD-L1 expression with the PTEN mutation, which may or may not lead to protein loss, and found that PTEN mutational status does not correlate with either PD-L1 expression (P ¼ 1) or PD-1+ TIL expression (P ¼ 1) (Fig. 4B) after false discovery rate correction.…”
Section: Garber Et Al: Pd-1/pd-l1 Expressionmentioning
confidence: 99%
“…4A). Because the IHC analysis does not take into account the confounding factor of PTEN expression in the tumor stroma, 18 we also evaluated the association of PD-L1 expression with the PTEN mutation, which may or may not lead to protein loss, and found that PTEN mutational status does not correlate with either PD-L1 expression (P ¼ 1) or PD-1+ TIL expression (P ¼ 1) (Fig. 4B) after false discovery rate correction.…”
Section: Garber Et Al: Pd-1/pd-l1 Expressionmentioning
confidence: 99%
“…1). Structural change is an important mechanism for inactivation of tumour suppressors in HGSOC, through heterozygous and homozygous loss 16 and gene breakage 17 . Approximately 50% of HGSOCs are defective in the homologous recombination (HR) DNA repair pathway 14,18,19 .…”
mentioning
confidence: 99%
“…More recently, ARID1A somatic mutation and concurrent protein expression loss have been identified in up to 50% of endometrioid carcinomas 7. Also, the tumour suppressor PTEN is mutated and the protein lost in almost 70% of endometrioid carcinomas; IHC downregulation for PTEN is also reported in up to 52% of HGSCs due to either homozygous deletion or hemizygous loss 8. Moreover, cyclin E1 expression and CCNE1 amplification have been reported in many HGSCs, but are absent in endometrioid carcinomas 9–11…”
Section: Looking At the Ovarymentioning
confidence: 99%